INTELLIGENCE CYCLE AS PART OF EFFECTIVE RISK ANALYSIS UNDER INTEGRATED BORDER MANAGEMENT - Livdāne, Jekaterina; Arbidāne, Iluta (Border Security and Management, 2020)
The aim is to present common approach of processing of information as one of the main aspects for qualitative risk analysis, including all three components – threat, vulnerability and impact, in all levels: strategic, operational and tactical. The theoretical methodology is based on guidelines of common integrated risk analysis model (CIRAM), implemented in Schengen member states (MS) as a part of integrated border management (IBM). Based on the main task – to view particular legal bases and using historical research, analytical and descriptive methods, the legal bases of IBM in the field of risk analysis was explained, at first. Special attention was paid for description of each step of intelligent cycle, because only scrupulous following of methodology guaranteed the high quality of the product in situations when analytical units have huge amount of data from different sources every day. Different kinds of risk analysis (annual, quarterly, monthly, weekly or targeted for specific measures) are performed by European Border and Coast Guard (EBCG) and MS using the CIRAM methodology. Huge data flows should be managed in a structured way. The knowledge and practical implementation of CIRAM has a positive impact on overall internal security in the area of free movement. For this purpose, the amount of trained border guards was analysed.